1999
DOI: 10.1209/epl/i1999-00470-4
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic ground state in La 0.5 Ca 0.5 MnO 3 thin films

Abstract: Resistivity and magnetisation measurements were done with bulk and thin-film samples of La 0.5Ca0.5MnO3. Bulk samples showed an antiferromagnetic insulating ground state as expected for this composition, whereas thin films demonstrated a ferromagnetic metallic ground state. This effect is attributed to the film adhesion to the substrate which prevents the lattice distortions necessary for the charge and antiferromagnetic ordering that occur in the bulk samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…when there is a large amount of strained grain boundary material present [37]. Similarly, a strained epitaxial film of La 0.5 Ca 0.5 M nO 3 was found to posess a FMM ground state [38], but this strain must be of the correct type [39]. These experiments demonstrate the important role of strain, which is expanded upon below and in the next sections on Landau theory.…”
Section: Phase Separation and Coexistencementioning
confidence: 98%
See 1 more Smart Citation
“…when there is a large amount of strained grain boundary material present [37]. Similarly, a strained epitaxial film of La 0.5 Ca 0.5 M nO 3 was found to posess a FMM ground state [38], but this strain must be of the correct type [39]. These experiments demonstrate the important role of strain, which is expanded upon below and in the next sections on Landau theory.…”
Section: Phase Separation and Coexistencementioning
confidence: 98%
“…Twinning may also be avoided by recourse to thin films. Remarkably, the proportions of two coexisting phases can be easily "tweaked" by external parameters that include pressure [51], magnetic fields [52], temperature [33,46], these three parameters together [53], strain [38], electrical currents [54] and X-ray [55] or electron illumination [56].…”
Section: Phase Separation and Coexistencementioning
confidence: 99%
“…However, experiments have also indicated that long ranged strain plays an important role. Insulating ordered phases appearing in bulk La 0.5 Ca 0.5 MnO 3 are suppressed in thin films 4 ; it is argued that the difference arises from the lattice mismatch with the substrate, which prevents the occurrence of lattice distortions necessary to accommodate orbital ordering. Similar conclusions have been drawn from recent work on Pr 0.6 Ca 0.4 MnO 3 films subjected both to compressive and tensile strain.…”
Section: Perovskitementioning
confidence: 99%
“…The sample was examined in a Philips CM30 microscope and was cooled to 90 K using a Gatan liquid nitrogen stage. The uniaxial stripe phase was identified via superlattice reflections in a selected area TEM diffraction pattern (illustrated below in Figure 2a); these reflections are detectable at 190 K, reaching a stable form at 90 K. (Note that previous resistivity measurements of thin film La 0.5 Ca 0.5 MnO 3 have failed to produce consistent results 11,12,13 , because of the difficulty of producing high quality films and a failure to check for the superstructure using a microscopic technique. )…”
mentioning
confidence: 99%